Phenotypic Antimicrobial Resistance Profiles of Human Campylobacter Species Isolated in Northwest Italy, 2020–2023 - Clara Tramuta; Aitor Garcia-Vozmediano; CeRTiS Clinical Laboratories Group; Cristiana Maurella; Daniela Manila Bianchi; Lucia Decastelli; Monica Pitti (Microorganisms, 2024)
The spread of antimicrobial resistant Campylobacter strains, linked to antimicrobials use and abuse in humans and food animals, has become a global public health problem. In this study, we determine the prevalence of antimicrobial resistance (AMR) in human Campylobacter isolates (n = 820) collected in Piedmont, Italy, from March 2020 to July 2023. The strains underwent susceptibility testing to determine the minimal inhibitory concentration for erythromycin, ciprofloxacin, gentamicin, streptomycin, and tetracycline: 80.1% of the strains showed resistance to at least one antibiotic. The highest prevalence of AMR was noted for ciprofloxacin and tetracycline (72.1% and 52.9%, respectively) and the lowest for erythromycin and aminoglycosides (streptomycin/gentamicin) (3.2% and 5.4%, respectively). The prevalence of co-resistance against fluoroquinolones and tetracyclines was 41.1%. The prevalence of multidrug resistant strains was 5.7%. Our data support evidence that AMR in human Campylobacter strains is common, particularly against ciprofloxacin and tetracycline, two medically important antimicrobials for humans.